(untitled) (Journal of Global Accounting, 2025)
This study examined sectoral differences in earnings management among non-financial firms in Nigeria, with focus on distinguishing between accrual-based earnings management and real earnings management through production and cash-flow channels. Using a balanced panel of listed non-financial firms, the study applied established earnings management proxies and employs descriptive statistics, panel analysis of variance (ANOVA), Bonferroni pairwise comparisons, and variance homogeneity diagnostics to identify sector-specific patterns. The results revealed pronounced sectoral heterogeneity. Accrual-based earnings management exhibits significant sectoral differences, with evidence of both income-decreasing and income-increasing accrual adjustments, depending on industry characteristics. In contrast, real earnings management is highly uneven and concentrated in specific sectors. In particular, the Health Care and Oil & Gas sectors exhibited consistently higher and more volatile real earnings management, driven largely by abnormal cash-flow manipulation. And in the case of Oil & Gas, abnormal production costs. Conglomerates and ICT firms, by contrast, displayed relatively low and stable levels of real earnings management. Pairwise correlations further indicated that accrual-based earnings management operates largely independently of real earnings management, while aggregate real earnings management is strongly driven by abnormal cash-flow activities. Overall, the findings suggest that while accounting standards and governance reforms may have constrained accrual manipulation, they have been less effective in limiting real activities manipulation, which carries direct economic costs. The study contributes to the literature by providing one of the first comprehensive sector-level analyses of multiple earnings management channels in Nigeria, highlighting the need for sector-specific regulatory oversight, enhanced operational monitoring, and risk-based audit and investment strategies in emerging markets.